Equipping Natural Killer Cells with Specific Targeting and Checkpoint Blocking Aptamers for Enhanced Adoptive Immunotherapy in Solid Tumors. Issue 29 (12th May 2020) - Zhang, Da; Zheng, Youshi; Lin, Ziguo; Liu, Xiaolong; Li, Juan; Yang, Huanghao; Tan, Weihong
Abstract: Herein, we propose an aptamer‐equipping strategy to generate specific, universal and permeable (SUPER) NK cells for enhanced immunotherapy in solid tumors. NK cells were chemically equipped with TLS11a aptamer targeting HepG2 cells and PDL1‐specific aptamer without genetic alteration. The dual aptamer‐equipped NK cells exhibited high specificity to tumor cells, resulting in higher cytokine secretion and apoptosis/necrosis compared to parental or single aptamer‐equipped NK cells. Interestingly, dual aptamer‐equipped NK cells induced remarkable upregulation of PDL1 expression in HepG2 cells, enhancing checkpoint blockade. Furthermore, in vivo intravital imaging demonstrated high infiltration of aptamer‐equipped NK cells into deep tumor region, leading to enhanced therapeutic efficacy in solid tumors. This work offers a straightforward chemical strategy to equip NK cells with aptamers, holding considerable potential for enhanced adoptive immunotherapy in solid tumors. Abstract : SUPER NK cells target cancer : An aptamer‐equipping strategy to generate s pecific, u niversal and per meable (SUPER) NK cells was reported for enhanced immunotherapy in solid tumors. SUPER NK cells were equipped with HepG2‐targeting and PDL1‐specific aptamers without genetic alteration, leading to effective homing to tumor sites, adaptation to the tumor microenvironment, and enhanced cytotoxicity.